Spatial Network Structure of the Global Tourism Economy: Global and Continental Perspectives From 1995 to 2019 - Yalan Shi; Miaojing Yu; Yongqing Cao; Yanxia Tan; Wenyue Liang (SAGE Open)
The spatial network of the global tourism economy has evolved into an increasingly complex system. However, no study has systematically captured and compared global and continental tourism economy network. This study objectively examines the spatial network structure of the global tourism economy from global and continental perspectives, by analyzing panel data from 142 major countries during 1995 to 2019, integrating a modified gravity model and social network analysis (SNA) method. Network density and network correlation of the global tourism economy have increased over time, with the global tourism economy network exhibiting stronger network and scale dependencies compared with the continental network. However, network density varied across five continents and was ranked as Europe > Africa > Asia–Oceania > the Americas. After 2000, global tourism economy network stabilized, forming 3 to 4 subgroups. However, the diffusion and spillover effects of core areas were restricted, the spatial connections of edge areas were weak. Additionally, the increasing and stable influence of “leader” countries and the decreasing and changing control ability of “middleman” countries suggested a trend toward direct tourism partnerships. A sustainable world tourism economy network calls for a clear role positioning of dominant, controlling and intermediary countries, and corresponding connectivity paths between the regions, policy recommendations for different countries.